Environmental enrichment with nylon gnaw sticks introduces variation in Sprague Dawley rat immune and lower gastrointestinal parameters with differences between sexes - Mark Wulczynski; Stephen P. J. Brooks; Judy Green; Fernando Matias; Martin Kalmokoff; Julia M. Green-Johnson; Sandra T. Clarke (Animal Microbiome)
Abstract Background Environmental enrichment (EE) is commonly included as an important component of animal housing to promote well being of laboratory animals; however, much remains to be learned about the impact of chewable forms of EE on experimental outcomes in the context of nutritional and microbiome-related studies, and whether outcomes differ between sexes. In the present study, nylon chew bones (gnaw sticks, GS) were evaluated for their effects on fermentation profiles, microbial community structure, and cytokine profiles of gastrointestinal and systemic tissues in pair-housed female and male Sprague Dawley (SD) rats. Results Food consumption and weight gain were not significantly altered by access to GS. Cecal short-chain fatty acid and branched-chain fatty acid profiles significantly differed between sexes in rats with access to GS, and alpha diversity of the microbiome decreased in females provided GS. Sex-related tissue cytokine profiles also significantly differed between rats with and without access to GS. Conclusions These findings indicate that including GS can influence microbiota and immune-related parameters, in a sex dependent manner. This shows that environmental enrichment strategies need to be clearly reported in publications to properly evaluate and compare experimental results, especially with respect to the use of chewable EE in the context of studies examining diet, microbiome and immune parameters.